A comparison of leptin and ghrelin levels in plasma and saliva of young healthy subjects - Aydin, S; Halifeoglu, I; Ozercan, IH; Erman, F; Kilic, N; Aydin, S; Caylak, E (Elsevier Science Inc, 2005)
In the last 10 years, saliva has been increasingly used as a diagnostic fluid and in predictions of disease progression. Leptin and ghrelin are synthesized in several tissues including the salivary glands. The action of ghrelin is antagonistic to that of leptin. This study was undertaken to measure and compare the saliva ghrelin-leptin and plasma ghrelin-leptin levels in healthy young subjects. In 30 healthy subjects, after an overnight fast, saliva and plasma leptin levels were measured using the ELISA method while saliva and plasma immunoreactive ghrelin levels were measured using a commercial radioimmunoassay (RIA). The latter uses I-125-labeled bioactive ghrelin as a tracer and a rabbit polyclonal antibody raised against full-length octanoylated human ghrelin (Phoenix, Europe, Karlsruhe, Germany). The results of this investigation revealed that saliva leptin levels (6.19 +/- 2.10 mu g/l) were lower than plasma levels (7.39 +/- 3.23 mu g/l) while saliva ghrelin levels (188.5 +/- 84.7 pg/ml) were higher than plasma levels (126.4 +/- 38.5 pg/ml), when male and female subjects were considered together. Saliva leptin levels (5.93 +/- 1.94 mu g/l) were lower than plasma levels (6.22 +/- 2.92 pg/ml) while saliva ghrelin levels (190.3 +/- 180.2 pg/ml) were higher than plasma levels (120.4 +/- 35.7 pg/ml) in young males. Saliva leptin levels (6.47 +/- 2.29 mu g/l) were lower than plasma levels (8.73 +/- 3.14 mu g/l) while saliva ghrelin levels (183.2 +/- 90.2 pg/ml) were higher than plasma levels (129.3 +/- 142.8 pg/ml) in young females, and both saliva and plasma leptin levels were slightly lower in male subjects in comparison with female subjects. Also, Immunohistochemistry study indicated that ghrelin positivity was found in ductus epithelium of salivary gland. We have demonstrated for the first time that saliva ghrelin levels were higher than in plasma while saliva leptin levels were almost the same as in plasma. Measurements of ghrelin and leptin in saliva is non-invasive, simple, and generally much preferred by patients and thus may be an acceptable alternative to plasma sampling. (c) 2004 Elsevier Inc. All rights reserved.
18th Meeting of the Turkish-Biochemical-Societies -- MAY 15-19, 2004 -- Trabzon, TURKEY
Keywords: ghrelin; leptin; saliva; plasma; immunohistochemistry